KANDUNGAN LOGAM Cu DAN Zn DALAM TANAH DAN PUPUK SERTA BIOAVAILABILITASNYA DALAM TANAH PERTANIAN DI DAERAH BEDUGUL - I Putu Meda Parmiko; I Made Siaka; Putu Suarya (Jurnal Kimia (Journal of Chemistry), 2014)
This research was carried out to determine the total metal concentrations of Cu and Zn in soil and inorganic fertilizer, as well as their bioavailabilities in the soil agricultural of Bedugul area. This study aims to determine the total metals and bioavailability of Cu and Zn in agricultural land in Bedugul. Analysis of the heavy metal contents of Cu and Zn in soil samples was started with the process of digestion the samples in a mixture of HNO3 and HCl (3:1) with an ultrasonic bath for 45 minutes at 60°C, followed by heating on a hotplate for 45 minutes at 140oC. Total metal concentrations of Cu and Zn in solutions resulted from digestion, extraction, and fertilizer samples were analyzed using Atomic Absorption Spectroscopy (AAS). The concentrations of Cu and Zn were calculated using a standard calibration method. Bioavailabilities of Cu and Zn were determined by comparing the results of a single extraction with HCl and EDTA to the total metal concentrations. The results obtained from 3 types of soil samples which were analyzed for determination of total Cu and Zn concentrations, showed that the highest Cu content was found in the land planted with tomatoes vegetables, 49.6437 mg/kg, while the highest total Zn contained in the land of carrot, i.e. 137,1457 mg/kg. TSP fertilizer contained Cu and Zn 29.3143 mg/kg and 186,2156 mg/kg respectively, whereas NPK fertilizer contained 16.9527 mg/kg of Cu and 168,3549 mg/kg of Zn. The percentage of Cu and Zn extracted by EDTA was the highest in the land of cabbage, followed by tomatoes land, and lastly carrots land, while Cu and Zn extracted by HCl in order of tomatoes land > cabbage land > carrot land.